Implementing a Web-enabled Security Management Information System: Opportunities and Challenges - David Jumpa Malem Sembiring; Devita Permata Sari Br Ginting; Sinek Mehuli Br Perangin-angin; Asprina Br Surbakti (LPPM STIKOM Tunas Bangsa, 2024)
Information systems are computer applications that support an organization's operations. They include the installation and maintenance of computers, software, and data. Management Information Systems focus on financial and personnel management. Sales Information Systems are designed to generate, analyze, disseminate, and retrieve information to support sales-related decisions. The collection, preparation, storage, and distribution of information to facilitate decision-making and monitoring in an enterprise. There are two types of information systems: manual information systems and computer-based information systems (CBIS). CBIS, or computerized web-based security service management information system, is a type of information system used in service companies. This system provides possibilities and opportunities for managing security services.